Comparison of the methods of fibrinolysis by tube thoracostomy and thoracoscopic decortication in children with stage II and III empyema: a prospective randomized study - Ufuk Cobanoglu; Fuat Sayir; Salim Bilici; Mehmet Melek (MDPI AG, 2011)
Today, in spite of the developments in imaging methods and antibiotherapy, childhood pleural empyema is a prominent cause of morbidity and mortality. In recent years, it has been shown that there has been an increase in the frequency of pleural empyema in children, and antibiotic resistance in microorganisms causing pleural empyema has made treatment difficult. Despite the many studies investigating thoracoscopic debridement and fibrinolytic treatment separately in the management of this disease, there is are not enough studies comparing these two treatments. The aim of this study was to prospectively compare the efficacy of two different treatment methods in stage II and III empyema cases and to present a perspective for treatment options. We excluded from the study cases with: i) thoracoscopic intervention and fibrinolytic agent were contraindicated; ii) immunosuppression or additional infection focus; iii) concomitant diseases, those with bronchopleural fistula diagnosed radiologically, and Stage I cases. This gave a total of 54 cases: 23 (42.6%) in stage II, and 31 (57.4%) cases in stage III. These patients were randomized into two groups of 27 cases each for debridement or fibrinolytic agent application by video-assisted thoracoscopic decortication (VATS). The continuity of symptoms after the operation, duration of thoracic tube in situ, and the length of hospital stay in the VATS group were of significantly shorter duration than in the streptokinase applications (P=0.0001). In 19 of 27 cases (70.37%) in which fibrinolytic treatment was applied and in 21 cases of 27 (77.77%) in which VATS was applied, the lung was fully expanded and the procedure was considered successful. There was no significant difference with respect to success rates between the two groups (P=0.533). The complication rate in our cases was 12.96% and no mortality was observed. Similar success rates in thoracoscopic drainage and enzymatic debridement, and the low cost of enzymatic drainage both served to highlight intrapleural streptokinase treatment as a reliable method in reducing the need for surgery in complicated empyema.